Role of Physical Activities during Working Hours in Promoting Planetary Health - Annukka Tapani; Elina Östring; Merja Sinkkonen (MDPI AG, 2024)
Work can be a source of a meaningful life and well-being. It can also be a source of stress and mental illness. The trends concerning working life development involve intensification and individualisation, and, at the same time, the demands of expertise work are such that they need collaborative actions. With respect to well-being, there is a need for individuals to see themselves members of the community. In this study, we identified vocational education staff types by studying the connections between physical activities and experienced workload. The data were collected by using empathy-based stories. The method of analysing the data can be described as a discursive-narrative approach based on qualitative and thematic content analyses. Based on the data, four story types were established: Forerunner, Exhausted, Leisure-Time Enthusiast, and Thinker. Individual conceptions of breaks, workload, free time, and awareness of one's well-being were found to be important in the creation of a healthy working life. There is a need to discuss realistic work demands in the vocational education context. Education and active teacher members could be key actors in achieving sustainability goals and improving planetary health.